The use of cannabis as an antiepileptic treatment in Mexico: A review, bioethical analysis, discussion and position of the Hospital General de México Epilepsy Clinic - M. Kalkach-Aparicio; M. Cuéllar-Herrera; E.L. Flores-Ramírez; P. Ruíz-Gadea; L. Medina-Osti; D. Trejo-Martínez; F. Velasco; G. Aguado; A.L. Velasco; G. Gorian-Montealegre (Revista Médica del Hospital General de México, 2016)
In Mexico and the United States of America (USA), a debate was recently opened on the use of some cannabis extracts as anticonvulsive drugs. Given the broad influence that social networks and the media have on the general population, it is worth highlighting the risk to the public of receiving erroneous information and forming opinions that may compromise their health. In light of this context, taxonomic and biochemical properties, the endocannabinoid system and the historical and legal context of cannabis were reviewed in order to provide a clear overview on the physiological and cultural impacts of cannabis extracts. Subsequently, pre-clinical models, clinical trials and ongoing studies evaluating some phytocannabinoids and synthetic cannabinoids as antiepileptic treatment were assessed. The obtained information was then subjected to interdisciplinary scrutiny and discussion. Taking into account that plantation and commercialisation of cannabis have been historically illegal in Mexico, the relative lack of evidence regarding its effects in humans and the ideas arising from the aforementioned, it is understandable that the medical community, as well as the general population, have reservations about its suitability as a treatment. Having developed a clinical neuroethics methodology, an interdisciplinary expert group discussion was coordinated in order to assess the benefits of the medical practice and limit the influence that healthcare professionals’ ethics could have on decision-making. This concluded with three proposals that portray the Hospital General de Mexico Epilepsy Clinic's position, while also contributing important considerations to the mature debate concerning the legalisation of cannabis.